2001
DOI: 10.1046/j.1365-2427.2001.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt change in primary productivity in a littoral zone of Lake Biwa with the development of a filamentous green‐algal community

Abstract: 1. Some characteristics of the photosynthesis and primary production of benthic and planktonic algal communities were investigated in a littoral zone covered with gravel in the north basin of Lake Biwa, paying special attention to the recent development of filamentous green algae (FGA) in the benthic algal community. 2. Pmax (maximum gross photosynthesis rate) values of the benthic algal community (0.1–1.2 mg C mg chl. a−1 h−1) obtained from photosynthesis–irradiance (P–I) curves were lower than those of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
3
21
0
1
Order By: Relevance
“…Therefore, the maximum benthic algal biomass in the stony zone of Lake Biwa was attributed to the appearance of Spirogyra sp. in recent years (Nozaki 1999(Nozaki , 2001Nozaki and Mitsuhashi 2000;Nozaki and Mitamura 2002). In the present study, the chlorophylla amounts in benthic algal communities increased from May to June, simultaneously with the propagation of the filamentous green algae Oedogonium sp.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Therefore, the maximum benthic algal biomass in the stony zone of Lake Biwa was attributed to the appearance of Spirogyra sp. in recent years (Nozaki 1999(Nozaki , 2001Nozaki and Mitsuhashi 2000;Nozaki and Mitamura 2002). In the present study, the chlorophylla amounts in benthic algal communities increased from May to June, simultaneously with the propagation of the filamentous green algae Oedogonium sp.…”
Section: Resultssupporting
confidence: 57%
“…Saijo et al (1966) investigated benthic algal communities dominated mainly by diatoms throughout the year in 1963-1964 in a littoral stony zone in the north basin of Lake Biwa and found a maximum biomass in February and a minimum in July to August. On the other hand, Nozaki (2001) investigated the chlorophyll-a of benthic algal communities formed on stones in a stony zone in the north basin of Lake Biwa from 1995-1996. The maximum values were obtained in June and July when a filamentous green alga, Spirogyra sp., appeared in abundance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Goldsborough and Robinson (1996) summarized the few available data of saturating irradiance (Ik) values (about 300-400 µmol photon m −2 s −1 ) in freshwater marsh assemblages. For Spirogyra, Nozaki (2001), on the other hand, observed the Ik values (150-200 µmol photon m −2 s −1 ) of a Spirogyra sp.-dominated community collected from a gravel zone in Lake Biwa. In addition, Nozaki and Mitamura (2002) showed that the photosynthesis-irradiance (P-I) curves of cultured Spirogyra were saturated at approximately 500 µmol photon m −2 s −1 under all water temperature conditions (25°-40°C).…”
Section: Discussionmentioning
confidence: 97%
“…Nozaki (2001) investigated benthic algal productivity in a gravel-covered littoral zone in that basin with special emphasis on the filamentous green algal community. Nozaki et al (2003) also reported on the development of benthic algae in a predominantly sand-beach area in Biwa's littoral zone.…”
Section: Introductionmentioning
confidence: 99%